United States : Selected Issues. (IMF Staff Country Reports; Country Report, 2005)
This Selected Issues paper on the United States examines the effect of the structure of the mortgage market on real housing activity and housing prices. The market-based financial structure has reduced the volatility of mortgage lending. Changes in the structure of the mortgage market have coincided with lower volatility of real housing activity. Regional income growth and unemployment rates have statistically significant and correct signed effects on housing prices. Tests of the relative importance of mortgage market structure and macroeconomic variables suggest an important effect from the financial structure.